Environmental Policy and Economies of Scope in Facility-Level Environmental Practices - Johnstone, Nick; Labonne, Julien; Thevenot, Celinc (2012)
In order to abate pollution, manufacturing facilities can either change their production processes (CPP) or introduce end-of-pipe technologies (EOP). The decision to undertake CPP rather than EOP is a reflection of the existence of economies of scope between production of the facility's conventional output and abatement of pollution. While this is determined by sectoral technological opportunities, facility size and other factors, environmental management practices, and public policy also play a role. Our results suggest that flexible instruments are more likely to result in CPP. We also provide insights on the role of environmental management, with the mainstreaming of environmental management within the firm leading to more integrated abatement strategies.